1978
DOI: 10.1107/s0567740878005014
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of triclinic WO3

Abstract: Between ca --40 and 17 °C tungsten trioxide, WO 3, has a pseudocubic triclinic crystal structure, space group Pi (C~), with a = 7.309 (2), b = 7.522 (2), c = 7.678 (2) A, a= 88.81 (2), fl = 90.92 (2), ~= 90.93 (2) °, V = 421.93 (9) A 3, and Z = 8. Intensity data for 2452 independent X-ray reflections from a single-domain crystal were measured on an automatic four-circle single-crystal diffractometer. From analogies with the crystal structure of the monoclinic room-temperature modification of WO3, the triclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(97 citation statements)
references
References 11 publications
6
91
0
Order By: Relevance
“…From the simple overlap analysis given thus far one would expect WO3 to have a cubic structure. In fact, even though WO3 undergoes at least four phase transitions between 0 and 950K, an octahedral tilting distortion is always present, along with a displacement of the tungstens from the center of the octahedra (Salje, 1977;Diehl, Brandt & Salje, 1978;Woodward, Sleight & Vogt, 1995). In this compound no A---O interactions are present, therefore, M--O bonding forces must be responsible for the observed distortions from cubic symmetry.…”
Section: Sno~-lattice Show That a 180 ° M---o---m Bond Anglementioning
confidence: 99%
“…From the simple overlap analysis given thus far one would expect WO3 to have a cubic structure. In fact, even though WO3 undergoes at least four phase transitions between 0 and 950K, an octahedral tilting distortion is always present, along with a displacement of the tungstens from the center of the octahedra (Salje, 1977;Diehl, Brandt & Salje, 1978;Woodward, Sleight & Vogt, 1995). In this compound no A---O interactions are present, therefore, M--O bonding forces must be responsible for the observed distortions from cubic symmetry.…”
Section: Sno~-lattice Show That a 180 ° M---o---m Bond Anglementioning
confidence: 99%
“…As for the WO]-portion of the Sb2WO6 structure, it would appear that all these polymorphs are characterized by essentially regular, corner-connected WO6 octahedra in which the W atoms are appreciably off-centre (Diehl, Brandt & Salje, 1978;Loopstra & Boldrini, 1966;Salje, 1977). A rather similar antiferroelectric pattern of tungsten movement to that observed in Sb2WO6 occurs in the room-temperature triclinic form of WO3 [viewed on its (101) plane (Diehl et al, 1978)]. The crystal chemistry underlying this phenomenon would appear to be an important problem in solid-state chemistry.…”
Section: Structure Refinement Of Sb2 W06mentioning
confidence: 99%
“…1. A monoclinic phase (P 2 1 /n) 60 [21] and a triclinic phase P1 exist at room temperature 61 [25,26]. At higher temperatures, Vogt et al [22] and Locherer 62 et al [19] concluded a transition from P bcn to the P 4/ncc 63 phase and Howard et al [23] observed an intermediate P 2 1 /c 64 phase.…”
mentioning
confidence: 99%